Chromatin associations in Arabidopsis interphase nuclei - Schubert, Veit; Rudnik, Radoslaw; Schubert, Ingo (Frontiers in genetics, 2014)
The arrangement of chromatin within interphase nuclei seems to be caused by topological constraints and related to gene expression depending on tissue and developmental stage. In yeast and animals it was found that homologous and heterologous chromatin association are required to realize faithful expression and DNA repair. To test whether such associations are present in plants we analyzed Arabidopsis thaliana interphase nuclei by FISH using probes from different chromosomes. We found that chromatin fiber movement and variable associations, although in general relatively seldom, may occur between euchromatin segments along chromosomes, sometimes even over large distances. The combination of euchromatin segments bearing high or low co-expressing genes did not reveal different association frequencies probably due to adjacent genes of deviating expression patterns. Based on previous data and on FISH analyses presented here, we conclude that the global interphase chromatin organization in A. thaliana is relatively stable, due to the location of its 10 centromeres at the nuclear periphery and of the telomeres mainly at the centrally localized nucleolus. Nevertheless, chromatin movement enables a flexible spatial genome arrangement in plant nuclei.
Keywords: expression; interphase nucleus; FISH; transcription; BAC; Arabidopsis; chromosome territory; chromatin association